The browser performance toolkit - Sweeney, Matt.; Safari eBooks; Velocity : web performance and operations conference (2010 : Santa Clara, Calif.) ([Calif.?] : O'Reilly Media, 2010)
"For many developers, the modern web site has evolved into something more like an application, requiring more specialized tools to measure performance. This video provides an overview of some of these tools. You will learn how to profile the loading and running of a web page in various browsers, identify performance bottlenecks, and examine ways to optimize the overall user experience. Vendor supported tools such as Firebug, Web Inspector, and IE Developer Tools are covered in addition to 3rd party software such as YSlow, PageSpeed, dynaTrace, and more"--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher.
Description from resource description page (viewed Aug. 30, 2010).
Keywords: Web site development -- Management; Browsers (Computer programs); Electronic books